Integrating a Unified Revenue Administration for Tax and Social Contribution Collections : Experiences of Central and Eastern European Countries. (IMF Working Papers; Working Paper, 2004)
During the 1990s, a failure to collect social contributions in Central and Eastern European countries deprived pension schemes of resources needed to meet their obligations. Based on these countries' experience, this paper examines the trend to increase coordination of tax and contribution collections. It sets out the rationale for establishing a unified agency as the best long-term strategy, and discusses policy and administrative issues in implementing this approach. The appendix presents three case studies for Albania, Bulgaria, and Romania, which are establishing a unified revenue administration. Another case study is presented for Sweden, which successfully integrated tax and social contributions collections in the 1980s.